2008
DOI: 10.1103/physreve.78.041404
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical heterogeneity in a model for permanent gels: Different behavior of dynamical susceptibilities

Abstract: We present a systematic study of dynamical heterogeneity in a model for permanent gels upon approaching the gelation threshold. We find that the fluctuations of the self-intermediate scattering function are increasing functions of time, reaching a plateau whose value, at large length scales, coincides with the mean cluster size and diverges at the percolation threshold. Another measure of dynamical heterogeneities-i.e., the fluctuations of the self-overlap-displays instead a peak and decays to zero at long tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 66 publications
(76 reference statements)
4
37
0
Order By: Relevance
“…Recent theoretical and simulation studies by Fierro et al [23,32] showed that the dynamics of permanent gels was also non-Gaussian at Fickian time scales and verified systematically that such non-Gaussian dynamics could be understood as a linear combination of the Gaussian displacement distribution functions of different values of D s , where D s is the diffusion coefficient of cluster size s of permanent gels. By employing the percolation theory and assuming the relation between D s and s, they proposed a quantitative theory to explain the complex dynamic behavior of gels in terms of P (D s ) and compared the theory to their simulation results.…”
Section: Introductionmentioning
confidence: 86%
“…Recent theoretical and simulation studies by Fierro et al [23,32] showed that the dynamics of permanent gels was also non-Gaussian at Fickian time scales and verified systematically that such non-Gaussian dynamics could be understood as a linear combination of the Gaussian displacement distribution functions of different values of D s , where D s is the diffusion coefficient of cluster size s of permanent gels. By employing the percolation theory and assuming the relation between D s and s, they proposed a quantitative theory to explain the complex dynamic behavior of gels in terms of P (D s ) and compared the theory to their simulation results.…”
Section: Introductionmentioning
confidence: 86%
“…First, we characterize the cooperative dynamics of the gels by means of the dynamical susceptibility χ 4 . This quantity has been extensively analyzed in numerical simulations of dense glassy systems [31], but it has been relatively less studied in gels [14,15,[32][33][34][35], in spite of the fact that experimental measures of χ 4 in colloidal gels have already been performed [15,32]. We compute χ 4 and its dependence on the scattering wave vector q in networks with varying density, discussing possible connections with experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…It is designed to capture the spatiotemporal correlations of particle nobilities and provides, from its peak value, an estimate of the dynamic correlations [50,52]. Such functions have also been analyzed for gels with permanent bonds [53] or low density gels [54].…”
Section: Heterogeneities In Dynamical Propertiesmentioning
confidence: 99%